Muscular activations during repetitions of sculling movements up to exhaustion in swimming - Rouard, A. H.; Billat, R. P.; Deschodt, V.; Clarys, J. P. (Archives of Physiology and Biochemistry, 1997)
The purpose of this study was to examine the influence of the repetition of sculling movements of the upper limb on muscular electrical activities during an exhaustive test in front crawl. Six upper limb muscles activities of nine swimmers were recorded, with telemetric EMG data acquisition system using active surface electrodes, during a 4 x 100 m front crawl test conducted to exhaustion. The pattern of the movement was analysed from views obtained by recordings of two underwater cameras. Four phases in the stroke were identified from the hand coordinates in the frontal plane (down-sweep, insweep, outsweep and recovery). Raw EMG were rectified, integrated (IEMG) and normalized for each subject and for each muscle with respect to the highest IEMG obtained during the strokes and the phases. Results indicated that the repetition of the stroke up to exhaustion was not associated with an increase in IEMG for the total stroke and its phases excepted for the most activated muscle. The different sculling movements appeared to be clearly identify by the EMG approach whatever the trial. The contribution of the different muscles remained the same through the different repetitions up to exhaustion. The larger muscular recruitments were obtained during the insweep phase when important antagonist activities were observed. It would be interesting to observe the EMG in a next 100 m repetition when the swimmer could not sustain the same velocity.